Prognosis and Prognostic Factors of Patients with Emergent Cerclage: A Japanese Single-Center Study - Ami Kobayashi; Hironori Takahashi; Shigeki Matsubara; Yosuke Baba; Shiho Nagayama; Manabu Ogoyama; Kenji Horie; Hirotada Suzuki; Rie Usui; Akihide Ohkuchi; Hiroyuki Fujiwara (Obstetrics and Gynecology International)
Objectives. The aims of this study were to clarify the following: (1) how often does prolonged pregnancy ≥34 weeks occur in patients with emergent cerclage without progesterone and (2) the risk factors preventing such pregnancy continuation. Materials and Methods. This retrospective observational study was performed using medical records of patients for whom emergent cerclage had been performed between April 2006 and December 2018 in our institute. Results. Emergent cerclage was performed in 123 patients (median age: 34, interquartile range: 31–36). Primiparous patients numbered 44 (36%). A history of spontaneous preterm birth (SPTB) was present in 30 (24%). The median presurgical cervical length (CL) was 16 (8–21) mm at surgery. Of the 123, 20 (16%) were delivered at 33 + 6 weeks or less (<34 weeks). We conducted logistic regression analysis of the risk factors of SPTBs <34 weeks after cerclage. Three risk factors were identified that increased the risk of SPTB <34 weeks: presurgical CL 0 mm (odds ratio (OR): 5.30; 95% confidence interval (CI): 1.58–17.7), a history of SPTB (OR: 4.65; 95% CI: 1.38–15.7), and the presence of sludge (OR: 4.14; 95% CI: 1.20–14.3). Conclusion. Three risk factors predicted SPTB <34 weeks after emergency cerclage without progesterone administration: unmeasurable CL (CL 0 mm), a history of SPTB, and the presence of sludge on ultrasound. SPTB <34 weeks occurred after emergency cerclage in 16% of patients, being comparable with the recent data with progesterone.